2020
DOI: 10.12701/yujm.2020.00626
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of multidrug-resistant tuberculosis

Abstract: Tuberculosis (TB) is still a major health problem worldwide. Especially, multidrug-resistant TB (MDR-TB), which is defined as TB that shows resistance to both isoniazid and rifampicin, is a barrier in the treatment of TB. Globally, approximately 3.4% of new TB patients and 20% of the patients with a history of previous treatment for TB were diagnosed with MDR-TB. The treatment of MDR-TB requires medications for a long duration (up to 20–24 months) with less effective and toxic second-line drugs and has unfavor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 43 publications
1
57
0
1
Order By: Relevance
“…Clofazimine is an antibiotic used to treat leprosy [ 111 ] and drug-resistant tuberculosis [ 112 ]. In 2016, Tuvshintulga et al reported that clofazimine has potent antibabesial effect, following its evaluation in B. microti -infected Balb/c mice.…”
Section: Novel Therapies Under Investigation For the Treatment Of Human Babesiosismentioning
confidence: 99%
“…Clofazimine is an antibiotic used to treat leprosy [ 111 ] and drug-resistant tuberculosis [ 112 ]. In 2016, Tuvshintulga et al reported that clofazimine has potent antibabesial effect, following its evaluation in B. microti -infected Balb/c mice.…”
Section: Novel Therapies Under Investigation For the Treatment Of Human Babesiosismentioning
confidence: 99%
“…If the isolate shows resistance to any of these drugs, then additions from group C can be used (ethambutol, delamanid, pyrazinamide, imipenem-cilastarin or meropenem, amikacin or streptomycin, ethionamide or prothionamide and para -aminosalicylic acid). Much like the treatment regimen, the duration can vary from patient to patient, taking up to 20 months in some cases [ 26 ].…”
Section: Tuberculosis: a Brief Overviewmentioning
confidence: 99%
“…About one fourth of population (10 million people) in the world is suffering from this disease, with death rates of 1.4 million people in 2019 (World Health Organization 2020). The emergence of multi-drug resistant TB (MDR TB), described as resistant to at least rifampicin and isoniazid, as the two most commonly applied powerful first-line anti-TB drugs, is also a major public health threat worldwide (Lange et al 2019) (Jang and Chung 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The phenotypic DST method is the gold standard for detection of drug resistance but this takes 2-3 months to yield results and also increases the risk of bacterial contamination and cross infection by non-tuberculous mycobacterial infection. To shorten the turnaround time, rapid molecular diagnostic polymerase chain reaction (PCR) and DNA sequencing methods were selected in this study (Genestet et al 2020;Li et al 2020;Jang and Chung 2020). The distribution of drug-resistant genes varies according to geographical locations and identifying the mutation patterns of MDR-TB is important to optimize the treatment protocol (Jaksuwan et al 2017) (Seifert et al 2015).…”
Section: Introductionmentioning
confidence: 99%